Phosphoinositol metabolism affects AMP kinase-dependent K-ATP currents in rat substantia nigra dopamine neurons - Shen, Ke-Zhong (Brain Res, 2018)
We reported recently that ligand-gated ATP-sensitive K(+) (K-ATP) current is potentiated by AMP- activated protein kinase (AMPK) in rat substantia nigra compacta (SNC) dopamine neurons. Because phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2) regulates K-ATP current, we explored the hypothesis that changes in PI(4,5)P2 modify the ability of AMPK to augment K- ATP current. To influence PI(4,5)P2 levels, we superfused brain slices with phospholipase C (PLC) activators and inhibitors while recording whole-cell currents in SNC dopamine neurons. Diazoxide, superfused for 5 min every 20 min, evoked K-ATP currents that, on average, increased from 38 pA at first application to 122 pA at the fourth application, a 220% increase. This enhancement of diazoxide-induced current was AMPK dependent because K-ATP current remained at baseline when slices were superfused with either the AMPK inhibitor dorsomorphin or the upstream kinase inhibitor STO-609. The PLC inhibitor U73122 significantly increased diazoxide current over control values, and this increase was blocked by dorsomorphin. Enhancement of diazoxide-induced current was also completely prevented by the PLC activator m-3M3FBS. Agonists at 5-HT(2C) and group I metabotropic glutamate receptors, both of which activate PLC, also prevented augmentation of diazoxide-induced current. Finally, inhibition of spike discharges by diazoxide was significantly antagonized by m-3M3FBS. These results suggest that PLC activity significantly influences the inhibitory effect of K-ATP channels by altering PI(4,5)P2 content. Results also suggest that modification of K-ATP current by PLC requires AMPK activity.